Simultaneous Determination of Succinic Acid and Water-Soluble Vitamins by Ion-Pair High-Performance Liquid Chromatography; Journal of Analytical Chemistry; Vol. 73, iss. 4 - Leonov K. A. Klim Andreevich (2018, 2018)
Title screen